TIPE1 inhibits osteosarcoma tumorigenesis and progression by regulating PRMT1 mediated STAT3 arginine methylation - Minghao Yang; Yuzhu Zhang; Guangping Liu; Ziqian Zhao; Jigang Li; Le Yang; Kui Liu; Wei Hu; Yunwei Lou; Jie Jiang; Qing Liu; Peiqing Zhao (Cell Death and Disease, 2022)
Abstract Osteosarcoma (OS), the most common primary malignancy of the bone, has a poor prognosis due to its high mortality rate and high potential for metastasis. Thus, it is urgently necessary to explore functional molecular targets of therapeutic strategies for osteosarcoma. Here, we reported that TIPE1 expression was decreased in osteosarcoma tissues compared to normal and adjacent nontumor tissues, and its expression was negatively related to tumor stage and tumor size. Functional assays showed that TIPE1 inhibited osteosarcoma carcinogenesis and metastatic potential both in vivo and in vitro. Furthermore, we investigated that the STAT3 signaling pathway was significantly downregulated after TIPE1 overexpression. Mechanistically, TIPE1 bind to the catalytic domain of PRMT1, which deposits an asymmetric dimethylarginine (ADMA) mark on histone/non-histone proteins, and thus inhibited PRMT1 mediated STAT3 methylation at arginine (R) residue 688. This abolished modification decreased STAT3 transactivation and expression, by which subsequently suppressed osteosarcoma malignancy. Taken together, these data showed that TIPE1 inhibits the malignant transformation of osteosarcoma through PRMT1-mediated STAT3 arginine methylation and ultimately decreases the development and metastasis of osteosarcoma. TIPE1 might be a potential molecular therapeutic target and an early biomarker for osteosarcoma diagnosis.